2003
DOI: 10.1111/1467-8624.00611
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chronic Peer Difficulties in the Development of Children's Psychological Adjustment Problems

Abstract: A longitudinal investigation was conducted to explicate how the confluence of early behavioral dispositions, relational histories, and cognitive representations of the self and others contributes to internalizing problems, externalizing problems, and loneliness. One-hundred and ninety three girls, and 206 boys were assessed annually from age 5 (kindergarten) to age 10 (Grade 4). Early aggressive behavior was related to Grade 4 maladjustment directly and indirectly through subsequent relational stressors. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
449
1
38

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(530 citation statements)
references
References 137 publications
33
449
1
38
Order By: Relevance
“…Indeed, it was found that children who are victimized tend to have increased levels of loneliness (Troop-Gordon and Ladd 2005), and decreased social satisfaction (Kochenderfer-Ladd and Wardrop 2001) compared to others. Moreover, children who are victimized may attribute victimization to their own deficiencies, potentially compromising their self-worth and precipitating depressive symptoms (Ladd and Troop-Gordon 2003;Troop-Gordon and Ladd 2005). Additionally, it has been shown that children who are depressed are more likely to be victimized (Kochel et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was found that children who are victimized tend to have increased levels of loneliness (Troop-Gordon and Ladd 2005), and decreased social satisfaction (Kochenderfer-Ladd and Wardrop 2001) compared to others. Moreover, children who are victimized may attribute victimization to their own deficiencies, potentially compromising their self-worth and precipitating depressive symptoms (Ladd and Troop-Gordon 2003;Troop-Gordon and Ladd 2005). Additionally, it has been shown that children who are depressed are more likely to be victimized (Kochel et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…And Hodges et al (1999) reported that victimization by peers predicted increases in internalizing and externalizing problems across the school year only for those children who lacked a mutual best friendship. Despite the reported relations between friendlessness and peer rejection and victimization, it is certainly the case that not all friendless children experience peer exclusion or victimization (Ladd and Troop-Gordon 2003). Accordingly, it could be that friendlessness and peer rejection or exclusion have markedly different effects on adjustment trajectories.…”
Section: Social Withdrawal and Individual Characteristics Friendshimentioning
confidence: 99%
“…Moreover, researchers have largely dispelled misconceptions that bullying is a normative childhood experience that has no, or minimal, effects on children's adjustment. Specifically, researchers have documented that victimized children are at risk for psychosocial problems including loneliness, low self-esteem and poor social relationships (Ladd & Troop-Gordon, 2003) as well as suicide, suicidal ideation and nonsuicidal self-injury (Bonanno & Hymel, 2010;Heilbron & Prinstein, 2010;Klomek, Marrocco, Kleinman, Schonfeld, & Gould, 2007). Further, bullied children tend to underperform academically (Juvonen, Wang, & Espinoza, 2011) and exhibit avoidant behaviors, such as developing negative school attitudes (Kochenderfer & Ladd, 1996a, 1996b, truancy, absenteeism and dropping out (Otieno & Choongo, 2010).…”
Section: To Tell or Not To Tellmentioning
confidence: 99%